Practices of and Perspectives on Palliative Sedation Among Palliative Care Physicians in Ontario, Canada: A Mixed-Methods Study - Amy Nolen; Debbie Selby; Fahad Qureshi; Anneliese Mills (Palliative Medicine Reports)
Background: Palliative sedation (PS) is a therapeutic intervention employed to manage severe and refractory symptoms in terminally ill patients at end of life. Inconsistencies in PS practice guidelines coupled with clinician ambiguity have resulted in confusion about how PS is best integrated into practice. Understanding the perspectives, experiences, and practices relating to this modality will provide insight into its clinical application and challenges within the palliative care landscape. Objective: The aim is to explore the perspectives of palliative care physicians administering PS, including how practitioners define PS, factors influencing decision making about the use of PS, and possible reasons for changes in practice patterns over time. Methods: A survey (n = 37) and semistructured interviews (n = 23) were conducted with palliative care physicians throughout Ontario. Codes were determined collaboratively and applied line-by-line by two independent investigators. Survey responses were analyzed alongside interview transcripts and noted to be concordant. Themes were generated through reflexive thematic analysis. Results: Five key themes were identified: (1) lack of standardization, (2) differing definitions, (3) logistical challenges, (4) perceived “back-up” to Medical Assistance in Dying, and (5) tool of the most responsible physician. Conclusion: There was significant variability in how participants defined PS and in frequency of use of PS. Physicians described greater ease implementing PS when practicing in palliative care units, with significant barriers faced by individuals providing home-based palliative care or working as consultants on inpatient units. Educational efforts are required about the intent and practice of PS, particularly among inpatient interprofessional teams.